Consumption and level of knowledge about electronic cigarettes among medical students (Research, Society and Development, 2024)
Objectives: Considering the increased prevalence of electronic cigarette use and its consequences on the health of users, this study was designed to evaluate the use and knowledge of EC among medical students at a university center in Northeastern Brazil. Methods: This is a cross-sectional observational study, in which sociodemographic data were collected through questionnaires applied to medical students from the first to the twelfth semester. Results: The survey included the participation of 248 students. It was observed that 25 undergraduates (10.1%) claimed to have high understanding about EC, 116 (46.8%) reported to have medium understanding, and 94 (37.9%) low level of knowledge. Furthermore, more than half of the students (53.2%) have already made use of the device. Of these, 38.7% reported vaporizing eventually and 14.5% vaporized daily. Conclusion: Therefore, we highlight the importance of an earlier and more complete approach about the harms of EC to undergraduate medical students to make them partners in the dissemination of information to lay people, including students from other courses and patients.